Legal Responsibility of Online Transport Platforms for Merchant Losses Due to Fictitious Orders by Online Transportation Drivers Perspective of Consumer Protection Law - Aprialdi, Ferby; Rahmad Efendi (Al-Risalah, 2025)
This study examines the legal responsibility of digital mobility platforms for merchant losses resulting from fictitious orders made by online transportation drivers, viewed from the perspective of consumer protection law. Using an empirical legal research method, the study combines normative analysis of laws such as the Consumer Protection Law and the ITE Law with field data obtained through interviews with the owner of the Burger Taqwa business. The findings reveal that fictitious orders often stem from weaknesses in the verification system and dishonest driver behavior. Although platforms like Gojek and Grab have implemented policies to delete fictitious orders and offer compensation, their enforcement is inconsistent and lacks transparency. Legal protections for merchants remain limited in practice, as the current regulatory and platform mechanisms prioritize end-consumers over business partners. The study highlights the need for stricter supervision, clearer legal accountability, and improved enforcement mechanisms to ensure fair protection for merchants in the digital economy ecosystem.